2022
DOI: 10.1088/1741-4326/ac8941
|View full text |Cite
|
Sign up to set email alerts
|

Global gyrokinetic simulations of ASDEX Upgrade up to the transport timescale with GENE–Tango

Abstract: An accurate description of turbulence up to the transport time scale is essential for predicting core plasma profiles and enabling reliable calculations for designing advanced scenarios and future devices. Here, we exploit the gap separation between turbulence and transport time scales and couple the global gyrokinetic code GENE to the transport-solver Tango, including kinetic electrons, collisions, realistic geometries, toroidal rotation and electromagnetic effects for the first time. This approach overcomes … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 104 publications
(171 reference statements)
0
13
0
Order By: Relevance
“…A quantitative analysis would require gyrokinetic simulations allowing the plasma profiles to self-consistently evolve due to the combined effect of turbulence and external particle and heat sources. These analyses will be performed in the near future, exploiting the recent GENE-Tango code coupling [21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A quantitative analysis would require gyrokinetic simulations allowing the plasma profiles to self-consistently evolve due to the combined effect of turbulence and external particle and heat sources. These analyses will be performed in the near future, exploiting the recent GENE-Tango code coupling [21].…”
Section: Discussionmentioning
confidence: 99%
“…Substantial speedups have been reported in the literature with such code coupling, enabling profile predictions with gyrokinetic codes. This (or similar approaches) is done both with flux-tube [7,35] and radially global gyrokinetic codes [21].…”
Section: Ion Temperature Peaking Due To Fast Particle Stabilizationmentioning
confidence: 99%
See 1 more Smart Citation
“…QuaLiKiz, hence its neural network regression, captures these effects. Regarding the problem of ion temperature saturation, it was found that the T e /T i dependence of turbulent transport was exacerbating this saturation [31]. It is therefore essential to explore the impact of larger T e /T i on turbulent transport and quantify its impact against collisional equipartition in explaining the T i saturation.…”
Section: Impact Of the Ion Turbulent Transportmentioning
confidence: 99%
“…Non-linear (gyro-) fluid models [7] can cover longer timescales, but besides the lack of kinetic effects, the deep non-linear evolution poses still some unresolved challenges. Also, direct coupling schemes of high-fidelity simulations and transport codes are presently developed [8], which however are also extremely costly. Therefore, robust reduced models for the analysis of stability and transport are needed as an additional tool.…”
Section: Introductionmentioning
confidence: 99%